FAKTOR RISIKO KEJADIAN HIPERTENSI PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKEMAS NAIBONAT - Maring, Feby Nonia Ayunda; Purnawan, Sigit; Ndun, Helga J.N. (Pusat riset dan Inovasi Nasional, 2022)
Hypertension or high blood pressure is a non-communicable disease that is one of the main causes of premature death worldwide. Generally, hypertension is found in people with old age, but in its development, hypertension also affects people of reproductive age, such as women of childbearing age. This study aimed to analyze the risk factors for hypertension in WUS in the working area of ​​the Naibonat Health Center. The type of research used is quantitative, with a case-control study approach. The case population in this study was 511 WUS, then 55 case samples were taken using a simple random sampling technique, and 55 control samples were taken from the respondent's closest neighbors. The data obtained were analyzed using the chi-square statistical test. The dependent variable in this study was hypertension, while the independent variables were age, family history, use of hormonal contraception, obesity, and stress. The results showed that three variables had a relationship with hypertension in women of childbearing age, namely age (p=0.000, OR=7.111), family history (p=0.002, OR=3.710), and physical activity (p=0.000, OR=4.495). in comparison, the use of hormonal contraception, obesity and stress did not have a relationship with the incidence of hypertension in women of childbearing age. The Puskesmas is expected to increase efforts to prevent hypertension by optimally improving services, especially in increasing public knowledge about hypertension so that people can maintain normal blood pressure and can avoid risk factors that can cause hypertension.